Controlling Syneresis of Hydrogels Using Organic Salts. (7th December 2021) - Panja, Santanu; Dietrich, Bart; Adams, Dave J.
Abstract: Supramolecular hydrogels can spontaneously undergo syneresis through fibre–fibre interactions and expel significant amounts of water upon aging. In this process, the hydrophobicity of fibres which regulates the 3D‐rearrangement of the self‐assembled structures during syneresis is important. Here, we show that we can control the hydrophobic microenvironment of gels by incorporating organic salts into the co‐assembled gel fibres thereby enabling control of the macroscopic gel volume phase transition. Abstract : For self‐shrinkable hydrogels, syneresis can be controlled by tuning the hydrophobic microenvironment within the gel network involving co‐assembly with organic salts.